Obuchenie gimnasticheskim uprazhneniyam na osnove ikh modelirovaniya - Ippolitov, Yu. A. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The purpose of this investigation was to elaborate the system of methods based on the mechanical-mathematical modelling for nstructing in gymnastic exercises. The original unificated methodics of biomechanical characteristic's defining had been elaborated as the result of the modelling researches. The classification of various biomechanical characteristics had been offered in connection with their function when motor action's structure forming. These new scientific conception can help to elaborate the new sports apparatus and training machines as well as the instrumental means of the corrective information.